Antisepsis for neuraxial procedures in Irish obstetric units and its possible impact on patient safety. A survey of national practice and associated complications. (May 2020) - Creaney, M.; Mac Colgáin, S.
Highlights: The AAGBI recommends 0.5% chlorhexidine gluconate for neuraxial antisepsis. One-fifth of Irish obstetric anaesthesia departments use 2% chlorhexidine gluconate. There is no evidence that 0.5% is safer than 2% chlorhexidine gluconate. We propose that application technique may be more important than choice of solution. Abstract: Introduction: The Association of Anaesthetists' guidelines recommend 0.5% chlorhexidine gluconate for skin antisepsis before obstetric neuraxial procedures. In this national survey, we identified the practice of all 19 obstetric units in Ireland. A secondary aim was to investigate complications in units not following guidelines. Methods: A consultant obstetric anaesthetist in each unit was asked seven questions relating to the antiseptic solution used, its application, their awareness of relevant guidelines, the unit epidural and caesarean section rates, and cases of either chemical arachnoiditis or central nervous system (CNS) infection in the previous year. Results: All units responded (n=6 incomplete data) and consented verbally to anonymous data use. Thirteen (68%) used 0.5% chlorhexidine and three used 2% chlorhexidine swab-sticks (ChloraPrep™) exclusively; a fourth used mostly 2% chlorhexidine while two units used povidone iodine exclusively (11%). There were no cases of chemical arachnoiditis. One of three reported infective complications was attributed in part to the antiseptic used (povidone iodine) and practice was subsequently changed. Conclusion: Twenty-one percent of obstetric anaesthesia units in Ireland, catering for one-third of the total deliveries, use the ChloraPrep™ swab-stick and consider it the safest form of application. Chlorhexidine gluconate has been implicated in devastating neurological injury, however there is no evidence that a less concentrated solution such as 0.5% is safer. We suggest a meticulous application technique should be considered more important for patient safety than the concentration of solution.